Pengaruh Lingkungan Sekolah Terhadap Pembentukan Karakter Siswa Pada Mata Pelajaran IPS Kelas V SD Negeri Daya 1 Makassar - Lirhan, Lirhan; Hamka, Nurwafiat (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2023)
The main objective of this research is to determine the influence of the school environment on the formation of student character in the social studies subject class V at SD Negeri Daya 1 Makassar. This type of research is correlational research which is used to determine the relationship and level of relationship between two. The population of this study was all students at SD Negeri Daya 1 Makassar, totalling 162 people. Meanwhile, the research sample was 25 class V students at SD Negeri Daya 1 Makassar. Data collection was carried out by distributing questionnaires and documentation. The data collected in the research was analyzed using inferential statistical techniques. Based on the results of the data analysis, it can be seen that the results of the school environment questionnaire were 1520 and the results of the character formation questionnaire were 1421. The results of the correlation data with 25 students had a correlation of 0.397 from the t table of 0.396. Thus, t count > t table, at a correlation coefficient level that is between 0.20-0.39, is considered a low level. This shows that the data analysis value is higher than the r table value, so the research hypothesis is accepted. Based on the research results, is the influence of the school environment on the formation of student character in social studies subjects for class V at SD Negeri Daya 1 Makassar.